Sustainability and productivity of Village Tank Cascade Systems: A bibliometric analysis and knowledge mapping - Ratnayake, Sujith S.; Reid, Michael; Larder, Nicolette; Kariyawasam, Champika S.; Hunter, Callum; Hunter, Danny; Dharmasena, Punchi B.; Pushpakumara, Gamini; Kogo, Benjamin (MDPI, 2024)
Research on social–ecological systems is rapidly expanding globally in response to human-induced climate change, biodiversity loss, and ecosystem degradation. Safeguarding these traditional agroecosystems is vital according to the 2030 Agenda for Sustainable Development. In the last decade, there has been a growing research interest in the Village Tank Cascade Systems (VTCSs) of Sri Lanka, recognised as social–ecological systems. However, few studies have systematically analysed VTCS research in Sri Lanka. To examine this apparent knowledge gap in more detail, a bibliometric analysis and knowledge mapping were conducted to systematically analyse and interpret the state, trends, clusters, and emerging fields of VTCS research. In total, 159 peer-reviewed research publications between 1985 and 2023 were obtained from the Web of Science Core Collection, Scopus databases, Google Scholar, and ResearchGate to perform this analysis. Furthermore, this study employed the Sustainability Assessment of Food and Agriculture systems (SAFA) tool, developed by the Food and Agriculture Organization of the United Nations, to map the inclusion of sustainability and productivity dimensions in VTCS research, in alignment with the objectives set forth by the 2030 Agenda for Sustainable Development. The study provides insight into dominant and neglected areas of future VTCS research.